Azacitidine versus decitabine in patients with refractory anemia with excess blast—Results of multicenter study. (June 2016) - Salim, Ozan; Toptas, Tayfur; Avsar, Esin; Yucel, Orhan Kemal; Ozturk, Erman; Ferhanoglu, Burhan; Geduk, Ayfer; Mehtap, Ozgur; Tombak, Anil; Tiftik, Eyup Naci; Deveci, Burak; Kurtoglu, Erdal; et al.
Highlights: Azacitidine or decitabine showed comparable ORR in patients with MDS-RAEB. The cumulative incidence of AML transformation at one year was comparable. Both agents have similar toxicity profiles. At least a four-cycle treatment with any HMA was a favorable factor. Abstract: The present study aimed to compare the efficacy and safety of azacitidine and decitabine in patients with myelodysplastic syndrome (MDS). A total of 88 patients diagnosed with refractory anemia with excess blast (RAEB) treated with azacitidine ( n   =  57) or decitabine ( n   =  31) were evaluated. Comparisons between azacitidine and decitabine groups were performed in the whole cohort, and in a 1:1 propensity score-matched cohort in order to reduce the simple selection bias. Patients who received azacitidine or decitabine had comparable overall response rates in both the unmatched (49.1% vs. 64.5%, p = 0.166) and the propensity-matched cohorts (52% vs. 68%, p = 0.248). The cumulative incidence of AML transformation at one year was comparable between azacitidine and decitabine in the unmatched (24.0% vs. 31.3%, p = 0.26) and in the propensity-matched cohorts (18.7% vs. 31.5%, p = 0.11). There was no difference in terms of transfusion requirement, febrile neutropenia episodes or the need for antifungal use during the treatment cycles in the propensity-matched cohort. The median overall survival was 20.4 months for azacitidine and 16.8 months for decitabine (p = 0.59). Finally, we found that at least a four-cycle treatment with any HMA was a favorable factor. In conclusion, both azacitidine and decitabine have similar efficacy and toxicity profiles in the treatment of MDS-RAEB.